Increasing the Plant Productivity Using the Automatic Controlled Irrigation System: A Comparative Experimental Study - Acar, Anıl Burak; Mengü, Hüseyin; Karatay, Seçil; Erken, Faruk (Ondokuz Mayis University, 2022)
With the development of technology, today, the use of technology in the field of agriculture has become widespread. In order to meet the increasing demand for agricultural products, automation techniques should be used in agricultural areas in order to make the production of agricultural products simpler and more efficient. In this study, an automation system is designed by making use of technology against problems such as irrigation problem and water shortage, which have become an important problem in agricultural areas. The data coming from the humidity sensor placed in the soil is processed to the controller. According to these processed data, when the soil is dry and the plant needs water, the water-pumping set automatically activates and meets the water needs of the plant. Optimum use of irrigation water to be used in agriculture is prevented unnecessary agricultural irrigation, reducing excessive water waste and providing a very high level of energy savings. At the same time, the negativities caused by excessive irrigation have been prevented. It is observed that the automatic controlled irrigation system used in this study saves a lot of water compared to the conventional irrigation system and increases the productivity of the plants to a great extent.
Keywords: Ziraat Mühendisliği; Agricultural Engineering; Drip irrigation; Automatic control; Productivity; Water savings; 2. Zero hunger; 6. Clean water